Kriminologisk læring af udviklingen i indbrud under pandemien - Peter Kruize; Britta Kyvsgaard (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract Our (work)lives have changed radically due to the Covid19-pandemic. This unique situation can be perceived as a natural experiment. What happens to the number of burglaries in private residences, businesses/companies, institutions, and holiday homes when many employees work from home and children receive online education? What are we to expect based on criminological theories and what happened in practice? Theory would predict a decrease in the number of burglaries in private homes and an increase in the number of burglaries in companies and institutions. In reality – at least in Denmark – there was a decline in all forms of burglary. The authors point to disruption of the market for stolen goods as a possible decisive factor in the explanation of this unexpected result.